2019
DOI: 10.1111/jop.12850
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of shammah (Arabian snuff) chewing to the risk of oral cancer and oral potentially malignant disorders

Abstract: Introduction Shammah is a form of smokeless tobacco commonly used in the Arabian Peninsula. The data on the harmful effects of shammah on oral health, particularly oral malignancies, are scarce. The aim of this review was to explore the association between shammah use and development of oral potentially malignant disorders (OPMD) and/or oral cancer. Materials and methods PubMed, EMBASE, Scopus, Web of Science and grey literature from January 1990 up to and including April 2018 were searched. Two independent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Shammah, also known as Arabian snuff, is a form of ST that is used in Yemen and Saudi Arabia, and is strongly associated with oral potentially malignant lesions and oral cancer [12,13]. On the grounds that the tongue is densely populated by a diverse microbial community [14], while it is also the most commonly affected site by oral cancer, including that associated with shammah use [15], the objective of this study was to explore the potential effect of chronic use of shammah, as an example of ST product, on the tongue microbiome in comparison to the tongue microbiome of shammah non-users.…”
Section: Introductionmentioning
confidence: 99%
“…Shammah, also known as Arabian snuff, is a form of ST that is used in Yemen and Saudi Arabia, and is strongly associated with oral potentially malignant lesions and oral cancer [12,13]. On the grounds that the tongue is densely populated by a diverse microbial community [14], while it is also the most commonly affected site by oral cancer, including that associated with shammah use [15], the objective of this study was to explore the potential effect of chronic use of shammah, as an example of ST product, on the tongue microbiome in comparison to the tongue microbiome of shammah non-users.…”
Section: Introductionmentioning
confidence: 99%
“…An African and Middle East based systematic analysis reviewed six studies and found shammah (form of SLT) had higher odds (39 times) of developing oral cancer. 10 Global burden analysis of SLT was performed for 127 countries including India. 11 This study pointed out that South Asian Region (India accounting for 70% of the load) is plagued with SLT pandemic with the highest mortality rate.…”
Section: Recent Literature Updates Smokeless Tobacco and Cancer: Clinical Studiesmentioning
confidence: 99%
“…ST known through different names such as: shammah (ordinary traditional ST), Hot (filter tobacco pouch ready to use sachet), Zarda (quid with smokeless tobacco), and others like toombak or neshoog, these are very popular in Yemen, Southern Saudi Arabia and Sudan [10,11,12,13]. The ST products are major risk factors of oral cancer, where shammah is strongly associated with oral potentially malignant and oral malignant lesions [14,15,16]. This study aims to evaluate the relationship between the use of smokeless tobacco and oral cancer.…”
Section: Introductionmentioning
confidence: 99%